Bronchial Epithelial Cells from Asthmatic Patients Display Less Functional HLA-G Isoform Expression - Carlini, Federico; Picard, Christophe; Garulli, Céline; Piquemal, David; Roubertoux, Pierre; Chiaroni, Jacques; Chanez, Pascal; Gras, Delphine; Di Cristofaro, Julie (Frontiers in Immunology, 2017)
Not all asthmatic patients adequately respond to current available treatments, such as inhaled corticosteroids or omalizumab®. New treatments will aim to target the bronchial epithelium-immune response interaction using different pathways. HLA-G is involved in immunomodulation and may promote epithelial cell differentiation and proliferation. HLA-G protein has several isoforms generated by alternative splicing that might have differential functionalities. HLA-G protein expression and genetic polymorphisms have been reported to be associated with asthma. Our hypothesis is that bronchial epithelium from asthmatic patients displays less functional HLA-G isoforms. HLA-G transcriptional isoforms were quantified by real-time PCR in HBEC grown in air-liquid interface culture obtained from 5 healthy controls (HC), 7 mild asthmatics (MA) and 7 severe asthmatics (SA). They were re-differentiated and IL-13 exposure was used as a proxy for a pro-inflammatory cytokine. HLA-G protein expression was assessed by western blot analysis. HLA-G allele was typed by direct sequencing. Our results showed that both MA and SA display less functional HLA-G isoforms than HC (p<0.05); in vitro HBEC re-differentiation from SA displays a particular isoform expression profile compared to MA and HC (p=0.03); HLA-G*01:06 frequency in MA and SA was significantly higher than in the healthy population (respectively p=0.03 and p<0.001); IL-13 exposure had no impact on HLA-G expression. Our results support that an impaired expression of HLA-G isoforms in asthmatic patients could contribute to the loss of inflammation control and epithelium structural remodeling. Therefore, HLA-G might be an interesting alternative target for asthmatic patients not adequately responding to current drugs.